Interfacial Properties of Aluminum/Glass-fiber Reinforced Polypropylene Sandwich Composites - Baştürk, S. B.; Tanoğlu, Metin; Guruşçu, A.; Tanoğlu, Metin (Springer Verlag, 2013)
Aluminum/glass-fiber-reinforced polypropylene (Al/GFPP) laminates were manufactured by using various surface pretreatment techniques. Adhesion at the composite/metal interface was achieved by a surface pretreatment of Al sheets with amino-based silane coupling agents, incorporation of a polyolefin-based adhesive film and modification with a PP-based film containing 20 wt.% of maleic-anhydride-modified polypropylene (PP-g-MA). In order to increase the effect of bonding between components of the laminates, the combination of silane treatment and the addition of the PP-based film was also investigated. The mechanical properties (shear, peel, and bending strengths) of adhesively bonded Al/GFPP laminates were examined to evaluate the effects of the surface treatments mentioned. It was revealed that the adhesion in the laminated Al/GFPP systems could be improved by the treatment of aluminum surface with an amino-based silane coupling agent. Judging from the results of peel and bending strength, with incorporation of polyolefin-based films, adhesion in the Al/GFPP laminates increased significantly. The modification of Al/GFPP interfaces with a PP-g-MA/PP layer led to the highest improvement in their adhesion properties. The combination of surface modification with silane and addition of PP-based films did not yield the high bending strength desired. This may be due to the insufficient bonding between silane groups and PP-based films.
Keywords: interface; adhesion; sandwich composite; mechanical properties